Diclofenac biodegradation by newly isolated Klebsiella sp. KSC: Microbial intermediates and ecotoxicological assessment - Stylianou, Kyriakos; Hapeshi, Evroula; Vasquez Christodoulou, Marlen; Fatta-Kassinos, Despo; Vyrides, Ioannis (My University, 2018)
The presence of diclofenac, a frequently used analgesic drug in the environment, can be harmful to a variety of organisms like algae, crustaceans and fish. In this study, a bacterial strain of Klebsiella sp. KSC (Gen Bank, accession number KX500307) able to biodegrade high concentration of diclofenac was isolated from livestock soil and identified. The exposure of Klebsiella sp. KSC to 70 mg/L of diclofenac resulted in diclofenac mineralization after 72 h. This is the first study that points out substantial biodegradation of high concentration of diclofenac (70 mg/L) in less than 72 h; and this shows the potential of this strain to be bioaugmented in contaminated sites or to bioreactors. The chemical structure of twelve biotransformation products of diclofenac are proposed. Its transformation pathway may involve hydroxylation, dehydroxylation, decarboxylation and dechlorination of the central ring of diclofenac. Acute ecotoxicity assay with Vibrio fischeri test showed that the main biotransformation product (TP298) of diclofenac by Klebsiella sp. KSC was less toxic than the parent compound.
Keywords: Biodegradation; Biotransformation; Diclofenac; Ecotoxicity assay; Klebsiella sp